The Cyclical Behavior of Marginal Cost and Price - Bils, Mark (American Economic Review, 1987)
This paper examines the cyclical behavior of price/marginal cost margins for U.S. manufacturing. Short-run marginal cost is markedly procyclical. In most industries, output price fails to respond to the cyclical movement in marginal cost; so price/marginal cost margins are markedly countercyclical. My results contradict business cycle theories that explain low production in a recession by a high real cost of producing; they support theories that explain low production in a recession by the inability of firms to sell their output.